DOP87 Multi-parameter datasets are required to identify the true prevalence of IBD: The Lothian IBD Registry (LIBDR). (25th January 2019) - Jones, G-R; Lyons, M; Plevris, N; Jenkinson, P; Bisset, C; Fulforth, J; Chuah, C S; Minnis, S; Gillespie, S-L; Brindle, W; Burgess, C; Henderson, P; et al.
Abstract: Background: A recent systematic review reports stabilising or falling IBD incidence in Western countries with an overall prevalence in excess of 0.3%. 1 However, the true prevalence may be under-reported due to incomplete ascertainment of cases. We therefore conducted an extensive multi-parameter search strategy, manually confirming all diagnoses through electronic patient record (EPR) review, to provide a robust point prevalence estimate for Lothian assessing the ability of data sources to identify true positives. Methods: Lothian is a well-defined geographical area in Scotland of 889450 people served by a single health board. All Scottish residents have a unique community health index (CHI) number for identification/linkage purposes. All regional pathology is coded for IBD in a single centre (1988–); all secondary care utilise a single EPR system for all patient interactions, all primary care prescribing is recorded centrally (2003–) as is secondary care prescribing of IBD biological drugs (2009–). We identified patients from the following sources; inpatient IBD codes (K50/51/52) ( n = 15879), IBD pathology codes ( n = 7313), IBD biological prescriptions ( n = 842), primary care 5'ASA prescriptions ( n = 5079) and an existing calprotectin database ( n = 7129) to identify 'possible' IBD cases to 31/08/18 (Figure 1A). Eight IBD physicians then manually screened the EPRs for all 'possible' cases to identify 'true' cases as per Lennard–Jones criteria, cross-referenced to all GI outpatient attendances in 2017 to assess completeness of data. In total, 24188 'possible' IBD cases were identified, manual review of patient EPRs revealed 14102 non-IBD diagnosis (Figure 1A). Results: The point prevalence of IBD in Lothian on 31/8/18 was 0.78% (CD; 283/100000, UC; 429/100000). Age (median, IQR) of the cohort was 49.3 (35.0–62.6) and 52.8 (39.6–66.2) years, age at diagnosis was 31.3 (21.7–48.9) and 38.1 (26.9–52.3) years and disease duration was 12.0 (6.1–20.9) and 11.2 (5.9–19.0) years for CD and UC, respectively. Age-group prevalence data for UC and CD is reported in Figure 1B. Pathology coding identified the most cases with >99% true positives and 72% of LIBDR patients overall. The inclusion of ICD K52 coding (IBDU, colitis unspecified etc.) reduced the accuracy of in-patient coding from 75 to 27% but in-patient coding overall only identified 55% of LIBDR patients (Figure 1C). Conclusions: We report a rigorously validated IBD cohort with all age point-prevalence of 0.78% on 31/8/18, one of the highest in Northern Europe. Reference 1. Ng SC. Worldwide incidence and prevalence of inflammatory bowel disease in the 21st century: a systematic review of population-based studies. Lancet 2018;10114:2769–2778.